Enzyme replacement therapy for alpha‐mannosidosis: 12 months follow‐up of a single centre, randomised, multiple dose study. Issue 6 (14th March 2013) - Borgwardt, L.; Dali, C. I.; Fogh, J.; Månsson, J. E.; Olsen, K. J.; Beck, H. C.; Nielsen, K. G.; Nielsen, L. H.; Olsen, S. O. E.; Riise Stensland, H. M. F.; Nilssen, O.; Wibrand, F.; et al.
Abstract: Background: Alpha‐mannosidosis (OMIM 248500) is a rare lysosomal storage disease (LSD) caused by alpha‐mannosidase deficiency. Manifestations include intellectual disabilities, facial characteristics and hearing impairment. A recombinant human alpha‐mannosidase (rhLAMAN) has been developed for weekly intravenous enzyme replacement therapy (ERT). We present the preliminary data after 12 months of treatment. Methods: This is a phase I‐II study to evaluate safety and efficacy of rhLAMAN. Ten patients (7–17 y) were treated. We investigated efficacy by testing motor function (6‐minutes‐Walk‐Test (6‐MWT), 3‐min‐Stair‐Climb‐Test (3‐MSCT), The Bruininks‐Oseretsky Test of Motor Proficiency (BOT2), cognitive function (Leiter‐R), oligosaccharides in serum, urine and CSF and Tau‐ and GFA‐protein in CSF. Results: Oligosaccharides: S‐, U‐ and CSF‐oligosaccharides decreased 88.6 % (CI −92.0 −85.2, p < 0.001), 54.1 % (CI −69.5‐ −38.7, p < 0, 001), and 25.7 % (CI −44.3‐ −7.1, p < 0.05), respectively.Biomarkers: CSF‐Tau‐ and GFA‐protein decreased 15 %, p < 0.009) and 32.5, p < 0.001 respectively.Motor function: Improvements in 3MSCT (31 steps (CI 6.8‐40.5, p < 0.01) and in 6MWT (60.4 m (CI −8.9 −51.1, NS) were achieved.Cognitive function: Improvement in the total Equivalence Age of 4 months (0.34) was achieved in the Leiter R test (CI −0.2‐0.8, NS). Conclusions: These data suggest that rhLAMAN may be an encouraging new treatment for patients with alpha‐mannosidosis.The study is designed to continue for a total of 18 months. Longer‐term follow‐up of patients in this study and the future placebo‐controlled phase 3 trial are needed to provide greater support for the findings in this study.